The circus age : culture & society under the American big top - Davis, Janet M. (University of North Carolina Press, 2002)
This work explores the development of the early 20th-century circus against developments such as the rise of big business and the genesis of the United States' overseas empire. It casts the circus as a powerful force in consolidating the nation's identity.